Analysis of erector spinae muscle fatigue in healthy subjects in the sitting position - Marcio Massao Kawano; Maryela de Oliveira Menacho; Beatriz Ito Ramos Oliveira; Marcela Carrilho Boer; Roger Burgo Souza; Jefferson Rosa Cardoso (Revista Brasileira de Cineantropometria e Desempenho Humano, 2009)
The aim of this study was to evaluate the frequency and amplitude of surface electromyography during erector spinae fatigue in healthy subjects in the sitting position. Eleven healthy males without low back pain participated in the study. The electromyographic parameters were collected with a surface electromyograph. Four electrodes were positioned lateral to the first and fifth lumbar vertebrae. The electromyographic signals were recorded during isometric trunk extension against a load cell in the sitting position. Loads of 50% and 75% of maximal voluntary isometric contraction were applied for 25 seconds to induce muscle fatigue. The signals processed using a Fast Fourier Transform algorithm and root mean square were submitted to linear regression to determine the fatigue index. The median frequency of the power spectrum presented negative values and the root mean square presented positive values, indicating muscle fatigue. No significant differences were observed when comparing level and side, or between loads (P > 0.05). The sitting position provides a better pelvis fixation and reproduces the usual position of occupational activities. The protocol used did not cause pain. Although all subjects presented erector spinae fatigue, no differences were observed between lumbar regions. The concomitant use of median frequency and root mean square in fatigue studies is suggested.